Sudden Fearful Death - Perry, Anne (Fawcett Columbine, 1993)
Victorian private inquiry agent William Monk is hired to investigate the brutal rape of a young London woman and the strangulation murder of Nurse Prudence Barrymore, a talented, extraordinary woman who had served in the Crimea with Florence Nightingale.
Keywords: Historical Mystery; Traditional Detective Mysteries